Anammox process for aquaculture waste water treatment: operational condition, mechanism,and future prospective - Ismail, Ismafatin Nabilah; Muhammad Taufik; Umor, N.A.; Mohamed Ramli, Norulhuda; Zulkarnaini, Zulkarnaini; Ismail, Shahrul (IWA Publishing, 2022)
Treatment of ammonia- and nitrate-rich wastewater, such as that generated in the aquaculture industry, is important to prevent environmental pollution. The anaerobic ammonium oxidation (anammox) process has been reported as a great alternative in reducing ammoniacal nitrogen concentration in aquaculture wastewater treatment compared to conventional treatment systems. This paper will highlight the impact of the anammox process on aquaculture wastewater, particularly in the regulation of ammonia and nitrogen compounds. The state of the art for anammox treatment systems is discussed in comparison to other available treatment methods. While the anammox process is viable for the treatment of aquaculture wastewater, the efficiency of nitrogen removal could be further improved through the proper use of anammox bacteria, operating conditions, and microbial diversity. In conclusion, a new model of the anammox process is proposed in this review.